2005
DOI: 10.1007/s10692-005-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Relaxation of Synthetic Fibres

Abstract: The stress regions where amplitude-modulated oscillations (AMO) appear, intensify, weaken, and disappear were determined for PET, Armos, SVM, Terlon synthetic fibres and monofilament PET fibres. The reappearance of AMO caused by the structure of the random copolymer was also found in Armos synthetic fibre. It was found for all fibres investigated that AMO do not appear at temperatures close to the glass transition temperature or any other softening point. A method is proposed for determining the temperature af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Numerous studies [1][2][3][4][5][6][7][8][9][10][11][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] carried out in different countries of the world showed the prospect of development in the energy efficiency industry. Broad experience was gained in performing parametric evaluations and successfully developing appropriate passive solutions for different climates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies [1][2][3][4][5][6][7][8][9][10][11][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] carried out in different countries of the world showed the prospect of development in the energy efficiency industry. Broad experience was gained in performing parametric evaluations and successfully developing appropriate passive solutions for different climates.…”
Section: Resultsmentioning
confidence: 99%
“…Methods of calculating capital costs for additional insulation, operating costs before and after thermal insulation, as well as the payback period of energy-saving measures are described in detail in the works [29][30][31][32][33]. To determine the simple payback, the following basic equation was obtained: (6) where ΔC -capital expenditures, rub.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the heat energy savings will be: -ΔQ ETICS = 367.7 Gcal/year after ETICS application, -ΔQ VFS = 311.5 Gcal/year after VFS application. Methods of calculating capital costs for additional insulation, operating costs before and after thermal insulation, as well as the payback period of energy-saving measures are described in detail in the works [15][16][17][18][19].…”
Section: Determination Of Transmission Heat Lossesmentioning
confidence: 99%
“…Taking into account the above-mentioned factors, the projected payback period of investment in additional facades insulation is determined by a logarithmic equation [15][16][17][18][19][20]. According to the equation the payback period of energy-saving measures was calculated taking into account the total capital expenditure for its implementation, the rising cost of tariffs for thermal energy (r), discounting future cash flows (i), achieved by cost-cutting as a result of the implementation of energy-saving measures.…”
Section: Determination Of Transmission Heat Lossesmentioning
confidence: 99%
“…Previously, in (Romanova et al 2000;2007b;Rymkevich et al 2014) for a number of studied polymer threads (SVM, lavsan, terlon, etc. ), it was found that in a certain range of mechanical stresses (or levels of static deformation) a complex non-exponential form of damped oscillations or beats schematically presented in Fig.…”
Section: Introductionmentioning
confidence: 99%